Identifying Metacognitive Online Reading Strategies Of Students Universitas Graha Nusantara - Harputra, Yuswin; Ramadhani, Yulia Rizki; Siregar, Muhammad Noor Hasan (Yayasan Kajian Riset dan Pengembangan RADISI, 2023)
The purpose of this study is to determine the metacognitive reading strategy EFL students of the English Department use during their academic period during this internet era. The participants were 76 English Education Study Program students from the academic year 2020/2021. Data came from the OSORS (Online Survey of Reading Strategy) questionnaire that provided accurate data. This study revealed that the students who participated in this study reported a wide range of metacognitive strategies when reading online academic texts. The Global Reading Strategies were the most popular metacognitive reading approach students use when reading online. The students participate in live chat with native speakers of English, where interacting with native speakers, the students can better grasp the native English language, phrases, and intonation by conversing with a native speaker. In keeping the reported use of strategies that include looking at sites covering both sides of an issue. The student searches for other areas that would analyze the topic, then combined his previous knowledge with information on the website. And the learners must have learned the first language. The role of L1 or its use is relevant in issues such as transfer or interference from L1 or even as a learning strategy in learning a second language.